Angle-scanned photoemission on YbHx: relevance for switchable mirrors - Hayoz, J.; Koitzsch, C.; Popovic, D.; Bovet, M.; Naumovic, D.; Aebi, Philipp (My University, 2002)
Yttrium, lantanum and rare earth elements can be loaded with hydrogen inducing a metal–insulator transition and giving rise to optical switching from reflecting to transparent. We present angle-scanned photoemission experiments characterizing thin YbHx films grown on W(110) at room temperature. Hydrogen loading is performed in an ultrahigh-vacuum-compatible high pressure (1 bar) reaction cell. Via full-hemispherical X-ray photoelectron diffraction and low energy electron diffraction, it is demonstrated that these films grow well-ordered and single-crystalline. Ultraviolet photoemission reveals a gap for the dihydride phase confirming a transition from reflecting to transparent as seen by visual inspection. Ion implantation through additional H+ sputtering allows one to increase the hydrogen content to x ≈ 2.4.